CDKN1B/p27 is localized in mitochondria and improves respiration-dependent processes in the cardiovascular system-New mode of action for caffeine. - Niloofar Ale-Agha; Christine Goy; Philipp Jakobs; Ioakim Spyridopoulos; Stefanie Gonnissen; Nadine Dyballa-Rukes; Karin Aufenvenne; Florian von Ameln; Mark Zurek; Tim Spannbrucker; Olaf Eckermann; Sascha Jakob; et al. (PLoS Biology)
We show that the cyclin-dependent kinase inhibitor 1B (CDKN1B)/p27, previously known as a cell cycle inhibitor, is also localized within mitochondria. The migratory capacity of endothelial cells, which need intact mitochondria, is completely dependent on mitochondrial p27. Mitochondrial p27 improves mitochondrial membrane potential, increases adenosine triphosphate (ATP) content, and is required for the promigratory effect of caffeine. Domain mapping of p27 revealed that the N-terminus and C-terminus are required for those improvements. Further analysis of those regions revealed that the translocation of p27 into the mitochondria and its promigratory activity depend on serine 10 and threonine 187. In addition, mitochondrial p27 protects cardiomyocytes against apoptosis. Moreover, mitochondrial p27 is necessary and sufficient for cardiac myofibroblast differentiation. In addition, p27 deficiency and aging decrease respiration in heart mitochondria. Caffeine does not increase respiration in p27-deficient animals, whereas aged mice display improvement after 10 days of caffeine in drinking water. Moreover, caffeine induces transcriptome changes in a p27-dependent manner, affecting mostly genes relevant for mitochondrial processes. Caffeine also reduces infarct size after myocardial infarction in prediabetic mice and increases mitochondrial p27. Our data characterize mitochondrial p27 as a common denominator that improves mitochondria-dependent processes and define an increase in mitochondrial p27 as a new mode of action of caffeine.